[Koek, Daniel (singer) : programs and related material collected by the National Library of Australia]
Material in the Australian performing arts programs and ephemera (PROMPT) collection consists of programs and related items for Australian performing arts organisations, Australian artists performing overseas, professional productions performed in Australia (including those featuring overseas performers) and overseas performances of Australian plays, music, etc.
Daniel Koek (pronounced 'Cook') was born in Gawler, South Australia, and studied Classical Voice and Japanese at the Conservatorium of Music, Adelaide. Daniel won the Young Achievers Award in 2003 and the coveted Young Artist Scholarship Program with the State Opera of South Australia. Upon moving to London he was awarded a place on the Musical Theatre Post Graduate Course at Mountview Academy of Theatre Arts. He is a tenor who known for his work in opera and musical theatre.
This collection is featured in the Guide to Australian Performing Arts Programs and Ephemera (PROMPT) Collections in the National Library of Australia
Keywords: Koek, Daniel -- Miscellanea; singers -- Australia -- Miscellanea; Theater programs -- Australia; Performing arts -- Australia; Printed ephemera -- Australia; Australian